Lapidus-Operation bei Patienten mit rheumatoider Arthritis--kurzfristig erreichte Ergebnisse - Popelka, S; Vavrík, P; Hromádka, R; Sosna, A (Zeitschrift fur Orthopadie und Unfallchirurgie, 2008)
AIM: Hallux valgus combined with flat foot is one of the most common foot deformities affecting patients with rheumatoid arthritis. The Lapidus procedure is indicated when the hallux valgus angle is more than 15 degrees or the first tarsometatarsal joint is hypermobile. We aimed to evaluate the results of the Lapidus procedure in patients with rheumatoid arthritis. METHOD: We performed the Lapidus procedure in 31 patients between 2002 and 2005. In ten patients we performed a bilateral procedure and in ten patients we performed a single Lapidus procedure. In 27 cases we combined the procedure with a resection of the second-fifth metatarsal heads (Hoffmann procedure), in four cases with a Weil osteotomy of the second-fifth metatarsal necks. We performed an excision of the articular surface of the first metatarsal head (Mayo) in 10 patients, a Keller resection procedure in 9 patients, an arthrodesis of the first metatarsophalangeal joint in 3 patients, and an Akin wedge osteotomy of the proximal phalanx of the thumb in 3 patients. Arthrodesis was fixed by two K-wires in 5 cases, by 2 compression screws in 7 cases, and in thirty-four cases we used memory staples. RESULTS: We evaluated the outcomes of forty-one procedures in thirty-one patients (24 female, 7 male). The averge age at surgery was 54.3 years. Thirty-two feet were without pain after the procedures, in five cases the patients felt moderate pain in the dorsal part of the foot and in four cases the patients felt pain in the transverse arch of foot. Complications included delayed primary wound closure in five cases, in one case we performed a revision procedure for a deep infection. Delayed hallux valgus developed in 5 cases. The mean first intermetatarsal angle before surgery was 19.5 degrees (range 12 - 27 degrees) and improved to 8 degrees after surgery. In 3 cases we found an unsatisfactory intermetatarsal angle correction with partial renewal of the hallux valgus. CONCLUSION: A correctly performed Lapidus procedure enables correction of the varus position of 1st metatarsus and hallux valgus.
Keywords: kostní dráty; sutura; Pain Measurement; Bone Screws; Flatfoot; Humans; Radiography; lidé středního věku; osteotomie; radiografie; Arthritis, Rheumatoid; Metatarsal Bones; Female; Hallux Valgus; lidé; reoperace; metatarzofalangeální kloub; artrodéza; Bone Wires; Arthrodesis; Metatarsophalangeal Joint; kostní šrouby; plochá noha; revmatoidní artritida; Postoperative Complications; pooperační komplikace; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Sutures; hallux valgus; metatarzální kosti; mužské pohlaví; Osteotomy; Reoperation; následné studie; měření bolesti